2021
DOI: 10.1038/s42003-021-02936-y
|View full text |Cite
|
Sign up to set email alerts
|

Rats exhibit age-related mosaic loss of chromosome Y

Abstract: Mosaic loss of the Y chromosome (LOY) is the most frequent chromosomal aberration in aging men and is strongly correlated with mortality and disease. To date, studies of LOY have only been performed in humans, and so it is unclear whether LOY is a natural consequence of our relatively long lifespan or due to exposure to human-specific external stressors. Here, we explored whether LOY could be detected in rats. We applied a locus-specific PCR and target sequencing approach that we used as a proxy to estimate LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…There is evidence from animal models that the rate of Y chromosome loss is tissue-dependent. By 2 years of age, rats develop LOY in the blood, brain, kidney, testis, and liver, but they do not develop LOY in the lung, muscle, pancreas, skin, or spleen [ 54 ]. Importantly, this study used qPCR of bulk tissue, which may miss LOY in underrepresented cell types.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from animal models that the rate of Y chromosome loss is tissue-dependent. By 2 years of age, rats develop LOY in the blood, brain, kidney, testis, and liver, but they do not develop LOY in the lung, muscle, pancreas, skin, or spleen [ 54 ]. Importantly, this study used qPCR of bulk tissue, which may miss LOY in underrepresented cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of Y-chromosome has been previously reported in other murine cell lines but never in a testicular-derived murine cell line. However, Y-chromosome instability has been found in rat and human testicular tumors [26][27][28], while the loss of the Y-chromosome was reported in the human testicular cell lines JKT-1 and TCam-2 [29,30], as well. The reason for this tumor-associated sex-chromosome loss remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…This common post-zygotic structural mutation shows a robust association with AD [151,152], contributing to disease through immune system dysfunction [150,153,154]. It has been hypothesized that as microglia proliferate, they could be more prone to LOY accumulation [155]. A recent study showed LOY is enriched in microglia from AD patients, resulting in dysregulation of many genes associated with aging and inflammation [156].…”
Section: Sources Of Microglial Sex Differencesmentioning
confidence: 99%